2018
DOI: 10.4110/in.2018.18.e35
|View full text |Cite
|
Sign up to set email alerts
|

Aryl Hydrocarbon Receptor Ligands Indoxyl 3-sulfate and Indole-3-carbinol Inhibit FMS-like Tyrosine Kinase 3 Ligand-induced Bone Marrow-derived plasmacytoid Dendritic Cell Differentiation

Abstract: Aryl hydrocarbon receptor (AhR) regulates both innate and adaptive immune responses by sensing a variety of small synthetic and natural chemicals, which act as its ligands. AhR, which is expressed in dendritic cells (DCs), regulates the differentiation of DCs. However, effects of AhR on the differentiation of DCs are variable due to the heterogeneity of DCs in cell surface marker expression, anatomical location, and functional responses. The plasmacytoid DCs (pDCs), one of DC subsets, not only induce innate as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…The AhR regulates both innate and adaptive immune responses and is expressed in dendritic cells (DCs). The AhR inhibits the development of plasmacytoid DCs from bone marrow precursors induced by FMS-like tyrosine kinase-3 ligand (Flt3L), probably via inhibition of signal transducer and activator of transcription-3 (STAT3) expression [79]. The study by Ghimire et al suggested an anti-inflammatory and tolerizing effect of IxS on human DCs [80].…”
Section: Indoxyl Sulfatementioning
confidence: 99%
“…The AhR regulates both innate and adaptive immune responses and is expressed in dendritic cells (DCs). The AhR inhibits the development of plasmacytoid DCs from bone marrow precursors induced by FMS-like tyrosine kinase-3 ligand (Flt3L), probably via inhibition of signal transducer and activator of transcription-3 (STAT3) expression [79]. The study by Ghimire et al suggested an anti-inflammatory and tolerizing effect of IxS on human DCs [80].…”
Section: Indoxyl Sulfatementioning
confidence: 99%
“…This effect was attributed to the suppression of STAT5 and STAT6 phosphorylation, which are transcription factors involved in Th2 differentiation. I3S can also induce T cell apoptosis, or programmed cell death, by upregulating the expression of pro-apoptotic proteins (192). Other indole derivatives, IAld and IPA, have also been shown to modulate immune responses by regulating T-cell function (193,194).…”
Section: Regulation Of Trp Metabolites From Gut Microbiota In the Ada...mentioning
confidence: 99%